The living earth [videorecording] - Discovery Channel (Quezon City : Magna Vision, 2004)
Explore what life was like on Earth hundreds of millions of years ago. Learn about the supercontinent Pangaea and how the planet's shifting plates of crust formed the world we know today. Then follow scientists as they uncover dinosaur fossils.
Elementary
Keywords: Planet Earth; Tectonic plates